2013
DOI: 10.1152/ajpgi.00375.2012
|View full text |Cite
|
Sign up to set email alerts
|

Laxative treatment with polyethylene glycol decreases microbial primary bile salt dehydroxylation and lipid metabolism in the intestine of rats

Abstract: van der Wulp MY, Derrien M, Stellaard F, Wolters H, Kleerebezem M, Dekker J, Rings EH, Groen AK, Verkade HJ. Laxative treatment with polyethylene glycol decreases microbial primary bile salt dehydroxylation and lipid metabolism in the intestine of rats. Am J Physiol Gastrointest Liver Physiol 305: G474 -G482, 2013. First published July 18, 2013; doi:10.1152/ajpgi.00375.2012.-Polyethylene glycol (PEG) is a frequently used osmotic laxative that accelerates gastrointestinal transit. It has remained unclear, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Laxatives accelerate gastrointestinal transit time and may have detrimental effects on the intestinal microbiota. van der Wulp et al previously showed that treatment with polyethylene glycol (an osmotic laxative) changes the composition of the intestinal microbiota and decreases the production of secondary bile acids in rats [ 28 ]. We also demonstrated that the use of cephalosporins, fluoroquinolones, and penicillin with β-lactamase inhibitors is significantly and independently associated with reductions in the relative abundance of Clostridiales Family XI Incertae Sedis representatives.…”
Section: Discussionmentioning
confidence: 99%
“…Laxatives accelerate gastrointestinal transit time and may have detrimental effects on the intestinal microbiota. van der Wulp et al previously showed that treatment with polyethylene glycol (an osmotic laxative) changes the composition of the intestinal microbiota and decreases the production of secondary bile acids in rats [ 28 ]. We also demonstrated that the use of cephalosporins, fluoroquinolones, and penicillin with β-lactamase inhibitors is significantly and independently associated with reductions in the relative abundance of Clostridiales Family XI Incertae Sedis representatives.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of strain-dependent profiles is also likely the reason we were unable to identify specific microbiome constituents which correlated with histological features of intestinal disease in this panel of mice. The intervention used to reduce the incidence of lethal intestinal plugs in the mice, the laxative PEGLYTE, may also have affected the microbiome data observed in CF and WT mice (van der Wulp et al 2013). Finally, although work to document the CF intestinal and pulmonary microbiomes is ongoing (O'Sullivan and Freedman 2009; Sun et al 2014a; Zhao et al 2012, Madan et al 2012), to date increased E. coli levels in fecal samples from CF children (Hoffman et al 2014) and for the lung, CF-associated bacteria including Pseudomonas aeruginosa and Staphylococcus aureus (Goddard et al 2012), as well as Streptococcus and Prevotella (Filkins et al 2012) have been reported, these bacteria were not prominent in the samples from CF mice studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding osmotic laxatives, it was found that alteration of the intestinal microbiome composition inhibits the metabolism of the primary bile salts, enhancing its excretion and modifying cholesterol metabolism, which delays its absorption [ 9 ]. Their results were also confirmed later by Strisciuglio et al's (2021) study [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chronic laxative use was reported to be associated with enhanced cholesterol conversion to bile acid and, consequently, lowering the serum level of both cholesterol and low-density lipoprotein-cholesterol (LDL-C) [ 8 ]. Polyethylene glycol (PEG) is an osmotic laxative that regulates cholesterol metabolism and modifies plasma levels [ 9 ]. In addition, the laxative drug elobixibat (an inhibitor of the ileal bile acid transporter) was associated with reduced LDL-C concentration in Japanese patients with chronic constipation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%